2015
DOI: 10.1111/ans.13320
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of high‐volume bariatric surgery in the public system

Abstract: Patients were older, heavier and suffered more co-morbid disease than previously reported cohorts. For the first time, excellent outcomes across a range of key quality domains in a large patient cohort have been reported in the public system. High-volume bariatric surgery in the public system is viable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
16
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 14 publications
4
16
0
Order By: Relevance
“…This finding fits in line with prior research that indicates that self‐modification tactics (such as diet and exercise) are associated with less WL than alternative means (such as bariatric or bypass surgery) and that individuals often report ‘disappointing’ WL results from self‐modification methods . Furthermore, a prior study reported an average patient satisfaction score of 7.7 (of 10) for bariatric surgery and past research indicates that bariatric surgery is associated with improvement in patient quality of life . Also, greater WL, better diet quality and increased physical activity have been found to be predictors of satisfaction with a WL program .…”
Section: Discussionsupporting
confidence: 85%
“…This finding fits in line with prior research that indicates that self‐modification tactics (such as diet and exercise) are associated with less WL than alternative means (such as bariatric or bypass surgery) and that individuals often report ‘disappointing’ WL results from self‐modification methods . Furthermore, a prior study reported an average patient satisfaction score of 7.7 (of 10) for bariatric surgery and past research indicates that bariatric surgery is associated with improvement in patient quality of life . Also, greater WL, better diet quality and increased physical activity have been found to be predictors of satisfaction with a WL program .…”
Section: Discussionsupporting
confidence: 85%
“…Four million adult Australians, or 27.2% of the adult population, were estimated to be obese in 2011-12, up from 19.1% in 1995. 7 Although obesity is more prevalent in areas of socioeconomic disadvantage 7 and surgical outcomes appear comparable by funding type, [8][9][10] >90% of bariatric surgery in Australia is privately funded (16 650 primary privately funded procedures were performed in 2015 11 ), a funding pattern that appears similar to that in other countries, such as Mexico and the United Arab Emirates. 12 Not all Australian jurisdictions provide publicly funded bariatric surgery and where it is available the waiting period can be prolonged.…”
Section: Introductionmentioning
confidence: 99%
“…These positive changes were achieved with a mean 18.5 kg weight loss (13.57% TBWL) at follow-up. This is a more modest weight loss than we have previously described at 5 years [ 29 ] but exceeds the level of weight loss we have previously shown to be correlated with significant health benefits at a threshold of 10%TBWL [ 27 , 30 ].…”
Section: Discussionmentioning
confidence: 45%
“…Two additional questions were asked regarding overall satisfaction with bariatric surgery and were derived from the validated Short Assessment of Patient Satisfaction (SAPS) questionnaire [ 27 , 28 ]. These were as follows: “how would you grade your satisfaction with bariatric surgery on a scale of 0–10?” and “how likely would you be to have the bariatric surgery again?”.…”
Section: Methodsmentioning
confidence: 99%